An Overview of the Avocado Market in the United States: FE1150, 8/2024 - Hammami, A. Malek; Huang, Kuan-Ming; Guan, Zhengfei (EDIS, 2024)
Driven by its healthy and nutritious attributes, the US avocado market has experienced tremendous growth over the past two decades. This publication provides a comprehensive overview of US avocado production and trade. The US avocado market, marked by the decline of already limited US domestic production, is increasingly reliant on imports, especially those from Mexico. This overview aims to inform industry stakeholders and policymakers of the current state of the industry and offer insights into its sustainability.